Phylogenetic analysis of Fusarium oxysporum f. sp. cubense associated with fusarium wilt of bananas from Peninsular Malaysia - Wong, Clement Kiing Fook; Dzarifah Zulperi,; Ganesan Vadamalai,; Noor Baity Saidi,; Teh, Chui Yao (Penerbit Universiti Kebangsaan Malaysia, 2019)
Fusarium wilt of bananas caused by Fusarium oxysporum f. sp. cubense (Foc) has been known to hamper banana production. In Malaysia, most of the edible banana cultivars are susceptible to the fungal strain Foc tropical race 4 (Foc TR4). To date, molecular characterisation of Foc TR4 in this country remains elusive. Thus, this study aimed to characterise the diversity of Foc TR4 in Peninsular Malaysia based on the phylogenetic analysis of transcription elongation factor (TEF-1α) sequences. From March 2016 to December 2016, 17 isolates of Foc were isolated from nine outbreak states in Peninsular Malaysia consisting of Penang, Perak, Selangor, Negeri Sembilan, Melaka, Johor, Pahang, Kelantan and Terengganu, with disease incidence exceeding 70% in several plantations. Morphological, molecular identification using TR4 specific primers and pathogenicity assay confirmed the identity of the fungal pathogen. Pathogenicity assays indicated that the aggressiveness level varies among the isolates. Phylogenetic analyses of TEF1-α sequences showed that there was no genetic variation among the Foc isolates by clustering them into four vegetative compatibility groups (VCGs) of 01213 (TR4), 01216 (TR4), 01213/16 (TR4) and 0121 (R4). PCR amplification using VCG specific primers have further categorised 16 Foc isolates as VCG01213 and a single isolate as VCG01213/16. In addition, no correlation between TEF-1α sequences and aggressiveness of isolates could be established.